Pengaruh Profitabilitas, Solvabilitas, dan Manajemen Laba terhadap Audit Delay pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2024 - Neli Amelia (AKUNTANSI 45, 2026)
This study is motivated by the importance of timely financial reporting in the Indonesian capital market, particularly in the property and real estate subsector which is prone to audit delay after the pandemic. Audit delay can reduce the relevance of information for investors and increase information asymmetry risk. The purpose of this study is to examine the effect of profitability (ROA), solvability (DAR), and earnings management (discretionary accrual using the Modified Jones Model) on audit delay in property and real estate companies listed on the Indonesia Stock Exchange during 2021–2024. This quantitative research employs a causal-comparative and explanatory approach. From a population of 91 companies, 59 companies were selected using purposive sampling (131 observations after outlier removal). Secondary data were obtained from annual financial reports published on the IDX website. Data were analyzed using multiple linear regression with SPSS Statistics 26 after classical assumption tests. The results show that profitability has a significant negative effect, solvability has a significant positive effect, and earnings management has a significant negative effect on audit delay. Simultaneously, the three variables have a significant effect with an Adjusted R² of 25.4%. The findings support Agency Theory. Companies are advised to improve transparency and reporting efficiency; future researchers are suggested to expand the sample, observation period, and include other variables such as firm size and auditor reputation.